Incidence des complications maternelles post opératoire de la césarienne à l’EHS Méré enfant de Laghouat 2024_2025 - Khiali Ahlam; Taher Safaa (université ammar telidji laghouat, 2025)
Abstract: Introduction: Caesarean section is an “artificial delivery in which the fetus is extracted through the maternal abdominal wall, in the most general sense, or very exceptionally through the vaginal wall whenever normal labor entails excessive risk to the mother or fetus, the major aim being such reduction in risk. The procedure introduces new risks, however.” In the old days, it was believed that the caesarean section was a “coat hanger” method and could only be used when all else failed. Today, the caesarean section is offered to many women for whom the diagnostic time was narrow. Until recently, the indications for it were limited to mechanical dystocia in the fetus and the blockage caused by the placenta previa. Like all surgery, it is associated with major complications that are often irreversible, and even death, particularly where infrastructure is poor and the conditions for safe surgery to address the complications are non-existent. No particular study has ever been performed at the EHS Maternity and Child Hospital in Laghouat focusing on the postoperative complications of cesarean sections before, which emphasizes the originality of the present study. The objective: A Study on Postoperative Complications of Caesarean Sections at the EHS Mother and Child Hospital in Laghouat Material and methods: This is a prospective descriptive study based on the detailed analysis of all maternal postoperative complications observed after caesarean section over four months from January 1, 2025, to April 30, 2025, in the wilaya of Laghouat. Results: From January 1st to April 30th, 2025, out of a total of 2,481 deliveries, we recorded 625 caesarean sections, representing a frequency of 25.19%. Among these 625 caesareans, 35 postoperative complications were identified, yielding an incidence of 5.60%. Among these complications 65.7% were non-infectious and 34.3% infectious. Details on composite postoperative morbidity subgrouping are presented in the following terms: Infections of the urinary system 22.9%, Anemia 22.9%, Hemorrhage 17.1%, Thrombocytopenia 11.4%, Wound suppuration 8.6%, Digestion problems 5.88%, Endometritis 2.9%, Anesthetic accidents 2.9%, Psychological complications 2.9 %, also, one maternal death case was observed in our study. Conclusion: The examination of this study's findings reveals that C-section is not a simple or (completely) risk-less solution, having, on the contrary, major maternal morbidity and in some women mortality. More accurate early detection of risk factors in addition to their prevention has potential to cut short maternal morbidities after cesarean and improve maternal outcome. Keywords: Post-caesarean morbidity, Causes of morbidity, Quality of care, Risk factors preventative
CD-ROM